1999
DOI: 10.1111/j.1574-6968.1999.tb13721.x
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional characteristics of heterotetrameric (α2β2) E1p of the pyruvate dehydrogenase complex fromZymomonas mobilis: expression from an own promoter and a lipoyl domain in E1β

Abstract: In the pyruvate dehydrogenase complex (PDHC) of Zymomonas mobilis the beta subunit of the pyruvate dehydrogenase (E1p) as well as the acetyltransferase (E2p) contain an N-terminal lipoyl domain. Both lipoyl domains were acetylated in vitro using 2-14C-pyruvate as a substrate, demonstrating that both lipoyl domains can accept acetyl groups from the E1 component. As previously shown the structural genes (pdhA alpha beta, pdhB, lpd) encoding the pyruvate dehydrogenase complex of Z. mobilis are located in two dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In most prokaryotic species, the LDs of PDH are always located in the E2 subunit dihydrolipoamide acetyltransferase (PdhC) (Perham, 2000). There are a few exceptions, such as the cases in Alcaligenes eutrophus (Hein and Steinbüchel, 1994) and Neisseria meningitidis (Bringas and Fernandez, 1995), where LDs were found in E3 subunit PdhD, while in Zymomonas mobilis, LDs were detected in pyruvate dehydrogenase E1 component subunit alpha (PdhA) (Ute et al, 1999). Our results indicated that the LD of M. hyopneumoniae PDH is in the PdhD subunit (Figures 2, 4).…”
Section: Discussionmentioning
confidence: 99%
“…In most prokaryotic species, the LDs of PDH are always located in the E2 subunit dihydrolipoamide acetyltransferase (PdhC) (Perham, 2000). There are a few exceptions, such as the cases in Alcaligenes eutrophus (Hein and Steinbüchel, 1994) and Neisseria meningitidis (Bringas and Fernandez, 1995), where LDs were found in E3 subunit PdhD, while in Zymomonas mobilis, LDs were detected in pyruvate dehydrogenase E1 component subunit alpha (PdhA) (Ute et al, 1999). Our results indicated that the LD of M. hyopneumoniae PDH is in the PdhD subunit (Figures 2, 4).…”
Section: Discussionmentioning
confidence: 99%